Tumor microenvironment and fibroblast activation protein inhibitor (FAPI) PET: developments toward brain imaging - Djekidel, Mehdi; Alsadi, Rahaf; Abi Akl, Maya; Bouhali, Othmane; O’Doherty, Jim (Frontiers in Nuclear Medicine, 2023)
Fibroblast activation protein (FAP) is a type-II membrane bound glycoprotein specifically expressed by activated fibroblasts almost exclusively in pathological conditions including arthritis, fibrosis and cancer. FAP is overexpressed in cancer-associated fibroblasts (CAFs) located in tumor stroma, and is known to be involved in a variety of tumor-promoting activities such as angiogenesis, proliferation, resistance to chemotherapy, extracellular matrix remodeling and immunosuppression. In most cancer types, higher FAP expression is associated with worse clinical outcomes, leading to the hypothesis that FAP activity is involved in cancer development, cancer cell migration, and cancer spread. Recently, various high selectivity FAP inhibitors (FAPIs) have been developed and subsequently used for positron emission tomography (PET) imaging of different pathologies. Considering the paucity of widely available and especially mainstream reliable radioligands in brain cancer PET imaging, and the poor survival rates of patients with certain types of brain cancer such as glioblastoma, FAPI-PET represents a major development in enabling the detection of small primary or metastatic lesions in the brain due to its biological characteristics and low background accumulation. In this work, we aim to summarize the potential avenues for use of FAPI-PET, from the basic biological processes to oncologic imaging and with a main focus on brain imaging.